2016
DOI: 10.1080/15257770.2016.1154969
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac nucleotide metabolism in Huntington's disease

Abstract: Huntington's disease (HD) is a monogenic neurodegenerative disorder with a significant peripheral component to the disease pathology. This includes an HD-related cardiomyopathy, with an unknown pathological mechanism. In this study, we aimed to define changes in the metabolism of cardiac nucleotides using the well-established R6/2 mouse model. In particular, we focused on measuring the activity of enzymes that control ATP and other adenine nucleotides in the cardiac pool, including eNTPD, AMPD, e5'NT, ADA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
(13 reference statements)
4
10
0
2
Order By: Relevance
“…Consequently, it has been shown that these cardiac pathologies might be caused by significant alterations in mitochondrial structure, including the loss of mitochondrial elongated shapes and diffused mitochondrial densities (Mihm et al, 2007 ; Kiriazis et al, 2012 ). Supporting this view of altered mitochondrial energy metabolism, we observed an increased level of purine catabolites in the heart mass of HD mouse models (Toczek et al, 2016a , b ). In addition, reactive oxygen species (ROS) play an important role in mitochondrial dysfunction, especially in skeletal muscle atrophy (Zuo et al, 2015 ; Zuo and Pannell, 2015 ) and heart failure (He and Zuo, 2015 ).…”
Section: Discussionsupporting
confidence: 76%
“…Consequently, it has been shown that these cardiac pathologies might be caused by significant alterations in mitochondrial structure, including the loss of mitochondrial elongated shapes and diffused mitochondrial densities (Mihm et al, 2007 ; Kiriazis et al, 2012 ). Supporting this view of altered mitochondrial energy metabolism, we observed an increased level of purine catabolites in the heart mass of HD mouse models (Toczek et al, 2016a , b ). In addition, reactive oxygen species (ROS) play an important role in mitochondrial dysfunction, especially in skeletal muscle atrophy (Zuo et al, 2015 ; Zuo and Pannell, 2015 ) and heart failure (He and Zuo, 2015 ).…”
Section: Discussionsupporting
confidence: 76%
“…In fact we showed that these catabolites were accumulated within the heart mass in the R6/2 mouse model [58]. In addition, these findings are supported by the observation of the up-regulation of genes involved in the adenosine degradation pathway, such as Ada or Dpp4.…”
Section: Discussionsupporting
confidence: 72%
“…These metabolites represent the first identified biomarkers related to striated muscle dysfunction in HD, in both pre-clinical and clinical settings ( Toczek et al, 2016b ). High-performance liquid chromatography assays demonstrate that enzymatic activity is also affected; AMPD and e5′NT exhibit decreased activity whereas ADA activity levels are increased, suggesting that mutant HTT could be disrupting cardiac nucleotide metabolism on a transcriptional level ( Toczek et al, 2016a ). Importantly, mutant HTT interacts with global gene regulators, such as HDACs, and this is potentially important for the gene expression changes observed in HD, as well as other types of cardiomyopathies ( Mielcarek et al, 2013 , 2015b ; Piotrowska et al, 2017 ).…”
Section: Heart Pathological Events In Symptomatic Hd Mouse Modelsmentioning
confidence: 99%